Superstable Theories and Representation - Shelah, Saharon (Sarajevo Journal of Mathematics, 2022)
In this paper we give an additional characterizations of the first order complete superstable theories, in terms of an external property called representation. In the sense of the representation property, the mentioned class of first-order theories can be regarded as "not very complicated". This was done for "stable" and for "$ {\aleph_0}$-stable." Here we give a complete answer for "superstable".